α-Galactosidase and Sucrose-Kinase Relationships in a Bi-functional AgaSK Enzyme Produced by the Human Gut Symbiont Ruminococcus gnavus E1 - Lafond, Mickael; Tauzin, Alexandra S.; Bruel, Laetitia; Laville, Elisabeth; Lombard, Vincent; Esque, Jérémy; André, Isabelle; Vidal, Nicolas; Pompeo, Frédérique; Quinson, Nathalie; Perrier, Josette; Fons, Michel; et al. (Frontiers in Microbiology, 2020)
Plant α-galactosides belonging to the raffinose family oligosaccharides (RFOs) and considered as prebiotics, are commonly degraded by α-galactosidases produced by the human gut microbiome. In this environment, the Ruminococcus gnavus E1 symbiont–well-known for various benefit–is able to produce an original RgAgaSK bifunctional enzyme. This enzyme contains an hydrolytic α-galactosidase domain linked to an ATP dependent extra-domain, specifically involved in the α-galactoside hydrolysis and the phosphorylation of the glucose, respectively. However, the multi-modular relationships between both catalytic domains remained hitherto unexplored and has been, consequently, herein investigated. Biochemical characterization of heterologously expressed enzymes either in full-form or in separated domains revealed similar kinetic parameters. These results were supported by molecular modeling studies performed on the whole enzyme in complex with different RFOs. Further enzymatic analysis associated with kinetic degradation of various substrates followed by high pressure anionic exchange chromatography revealed that catalytic efficiency decreased as the number of D-galactosyl moieties branched onto the oligosaccharide increased, suggesting a preference of RgAgaSK for RFO’s short chains. A wide prevalence and abundance study on a human metagenomic library showed a high prevalence of the RgAgaSK encoding gene whatever the health status of the individuals. Finally, phylogeny and synteny studies suggested a limited spread by horizontal transfer of the clusters’ containing RgAgaSK to only few species of Firmicutes, highlighting the importance of these undispersed tandem activities in the human gut microbiome.